Stefan Swieżawski at the Catholic University of Lublin - Gut, Przemysław (Roczniki Filozoficzne, 2025)
This article presents the profile of Professor Stefan Swieżawski in the context of his academic activity at the John Paul II Catholic University of Lublin. It discusses his most important scholarly and organizational achievements related to his work at the university, demonstrating that, from the perspective of the university’s hundred-year-long history, Swieżawski is among its most outstanding and influential professors. The article also emphasizes that, to a large extent thanks to his dedication, the Faculty of Philosophy at KUL, after World War II, was transformed into a major center of philosophical research of a national scale, and became an important hub for studies in medieval philosophy and the intellectual heritage of 15th-century European thought.